ความพึงพอใจของผู้เรียนต่อ หลักสูตรแพทยศาสตรบัณฑิต หลักสูตรปรับปรุง พ.ศ. 2557 คณะแพทยศาสตร์ศิริราชพยาบาล - แสงแก้ว, พชร (Siriraj Medical Bulletin, 2018)
Objective: This study examined the students’ satisfaction towards Doctor of Medicine Program, revised curriculum 2014 of Faculty of Medicine Siriraj Hospital. The study focused on course contents, teaching activities, teaching support factors, measurement and evaluation, and lecturers. Methods: The survey sample included 292 medical students of second and third-year students. Questionnaires were used to collect data and the data was analyzed using statistics such as percentage, arithmetic mean, and standard deviation. Results: The results revealed that students were highly satisfied with the Doctor of Medicine Program in all five aspects. The highest average was lecturers aspect (mean=4.12), measurement and evaluation (mean=3.79), course contents (mean=3.72), teaching activities (mean=3.59) and teaching support factors (mean=3.52). Conclusion: The overall opinions of the medical students were found that lecturers are the most significant key factors of Doctor of Medicine Program learners.